REAKTUALISASI PRINSIP MASLAHAT DAN KEADILAN SOSIAL DALAM KONTEKSTUALISASI FIKIH ZAKAT - Rahmat Hakim, Budi; Nafi, Muhammad; Hidayatullah, Hidayatullah; Herlinawati, Herlinawati (Universitas Islam Negeri Antasari Banjarmasin, 2024)
As a text, Muslims agree that zakat is a pillar and ritual of Islam that every Muslim is obligated to perform. Nevertheless, as a form of text-ritual, zakat will always be contextualized. He is always tied to the culture of the community where the zakat ritual is performed. That is, the implementation of zakat is very likely to vary, depending on how the meaning of zakat is interpreted and reinterpreted by local communities. The law of zakat is different from other laws of worship, because the nature of the law at this level is flexible, dynamic and elastic in accordance with the development and needs of society (mu'amalah ijtima'iyyah) which is based on normative passages that are general and zanniyyah. This paper seeks to analyze and find applicative ideas about the theory of maslahat and social justice in various concepts of contemporary scholarly thought to then be correlated with the formulation of the development of ijtihad zakat based on maslahat and justice. A number of relevant references are used as sources as well as material for conducting critical analysis with a qualitative descriptive approach so that it can be emphasized the building of ideas and strategic steps to make zakat an Islamic social system that not only touches the question of creed alone, but also the socio-economic welfare of the community as well as the great purpose of zakat sharia.